“Lawan” Orang Yehuda Dan Benyamin: Sebuah Tinjauan Terhadap Teks Ezra 4:1-3 - Wijaya, Jonathan (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2024)
Abstract:Inevitably, the author of the book of Ezra did not write without a reason or agenda. Because it is clear that the writing of the book of Ezra is historiographic, this means that the writer of the book of Ezra had a purpose when he wrote and identified the people who wanted to help the tribes of Judah and Benjamin (from the land of exile) in the process of building the Temple of God as "opponents". So, why did the book's writer of Ezra identify them as “opponents”? With the steps of investigating the Old Testament by focusing on investigating the term "opponent" by paying attention to the historical context and context of the text, to produce a clear identity of the term "opponent", the author will show that the aim of the author of the book of Ezra was to invite his readers to a holy life. Means not being polluted by those who worship other than YHWH. Moreover, our writer Ezra wants to show that their bid to build the Temple had a plan to thwart the construction. To achieve this, the author will divide this article into four parts. First, the author will explain the historical context of Ezra 4:1–4. Second, the author will explain the textual context of Ezra 4:1–4. Third, the author will present the interpreter's view regarding Ezra 4:1–4. Finally, the author will conclude that the people of Judah and Benjamin did not want to blend in and involve them ("opponents") in the construction to maintain their holiness and the Temple of God. In addition, the identity of the “opponents” of the people of Judah and Benjamin is proven by the delay in constructing the Temple, approximately 20 years (cf. Ezra 3:3; 4:4–24). AbstrakTidak dapat dielakkan, penulis kitab Ezra tidak menulis tanpa ada alasan dan agendanya. Sebab nyata tulisan kitab Ezra bersifat historiografi. Itu berarti bahwa penulis kitab Ezra memiliki tujuan ketika ia menulis maupun mengidentifikasi orang-orang yang ingin membantu suku Yehuda dan Benyamin (dari tanah pembuangan) dalam proses pembangunan Bait Allah sebagai “lawan”. Lantas, apa alasan penulis kitab Ezra mengidentifikasi mereka sebagai “lawan”? Dengan langkah-langkah penyelidikan Perjanjian Lama dengan fokus pada penyelidikan istilah “lawan” dengan memperhatikan konteks historis dan konteks teks, sehingga dihasilkan identitas yang jelas dari istilah “lawan”, penulis akan menunjukkan bahwa tujuan penulis kitab Ezra adalah untuk mengajak pembacanya untuk hidup kudus yang berarti tidak tercemar dengan mereka yang menyembah selain YHWH. Selain itu, penulis kita Ezra ingin menunjukkan bahwa tawaran mereka untuk membangun Bait Allah memiliki suatu rencana untuk menggagalkan pembangunan itu sendiri. Untuk mencapai hal tersebut, penulis akan membagi tulisan ini menjadi empat bagian. Pertama, penulis akan memaparkan konteks historis Ezra 4:1–4. Kedua, penulis akan memaparkan konteks tekstual dari Ezra 4:1–4. Ketiga, penulis akan menyampaikan pandangan penafsir mengenai Ezra 4:1–4. Terakhir, penulis akan memberikan kesimpulan bahwa orang Yehuda dan Benyamin tidak ingin membaur dan melibatkan mereka (“lawan”) di dalam pembangunan tersebut untuk menjaga kekudusan mereka, serta Bait Allah. Selain itu, identitas “lawan” orang Yehuda dan Benyamin terbukti dengan terhambatnya pembangunan Bait Suci, kurang lebih 20 tahun (lih. Ezra 3:3; 4:4–24).